THE EFFECT OF MARKETING MIX ON DAIHATSU CAR PURCHASE DECISIONS IN PT. ASTRA INTERNATIONAL KARAWANG - Isyanto, Puji; Mulyadi, Dedi; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
Marketing is an important factor in the development of the company. Good marketing is done throngh product, price, place, and promotion. Lack of knowledge of consumer taste are changing or dynamic, and ineffective marketing strategies implemented will affect less well on achievement target market. Purpose of this study was to determine the effect of product, price, price, place,and promotion in the PT. Astra International Karawang. Type of associative research study used the method to search for a correlation causal relationship (causal relationship). Consumers with a population 531 samples of 84 respondents. Methods of analysis used multiple linear analysis. Results of research conducted simultaneous product, price, place, promotion significantly influence purchasing decisions on the PT. Astra Karawang. Partially or significantly influence produc, price, place, and promotion purchasing decisions. Powerful variable is the product, price, and place, and for the weak variable is a variable promotion.